A note on a pygmy right whale (Caperea marginata) sighting in the southwestern Pacific Ocean - Matsuoka, Koji; Pitman , Robert L.; Marquez , Fernanda F. C. (J. Cetacean Res. Manage., 2023)
There are no previously published sightings of pygmy right whales (Caperea marginata) from the southwest Pacific Ocean. This note reports a sighting of 14 pygmy right whales approximately 445km southeast of Christchurch, New Zealand, at 17:30 on 5 January 2001 (46°26’S, 177°18’E). No cow-calf pairs were observed. Although feeding was not directly observed, several animals defecated during the observation period. The faeces were bright red and formed into small red clumps that bobbed at the water’s surface which implies that the whales had recently been feeding in the immediate area. It appears that pygmy right whales may aggregate at the Sub-tropical Convergence during the austral summer and that this area may represent an important feeding ground.